Green Synthesis of Silver Nanoparticles using Acalypha indica L. Extract Obtained by Subcritical Water Extraction - Poopeerasupong, Sompoch; Sunphorka, Sasithorn; Wintachai, Mongkon; Khangkham, Supaporn (Journal of Advanced Development in Engineering and Science, 2023)
This study focused on the green synthesis of silver nanoparticles using Acalypha indica L. extract obtained by subcritical water extraction as a reducing agent. The Box-Behnken experimental design was applied for evaluating the influence of extraction process parameters namely temperature, initial pressure and operating time on total phenolic content of the extract. The results showed that the total phenolic content of the extract significantly depended on temperature and duration, and attained its maximum at 200 oC, initial N2 pressure of 1 bar and 60 minutes of extract duration. The synthesis of silver nanoparticles was then investigated under various reaction temperatures, concentrations of AgNO3 and reaction times. It was found that increasing temperatures and concentrations of AgNO3 led to an increase in size of the particles. The optimal condition for silver nanoparticles synthesis was 50 oC, 0.010 mol/l of AgNO3 solution and 180 minutes, at which the spherical silver nanoparticles with diameters of 1 to 30 nm could be obtained. Moreover, the results also revealed that Acalypha indica L. extract could help prevent or inhibit particle agglomeration.